Changes in Anesthesia-Related Factors in Ambulatory Knee and Shoulder Surgery: United States 1996-2006. Issue 4 (1st June 2011) - Memtsoudis, Stavros G.; Kuo, Cassie; Ma, Yan; Edwards, Alison; Mazumdar, Madhu; Liguori, Gregory
Abstract : Background: Analyses of existing nationally representative information on how changes in ambulatory orthopedic surgery have affected anesthesia practice over time are rare. We sought to characterize temporal changes in factors surrounding ambulatory orthopedic surgery and anesthesia. Methods: Data from the National Survey of Ambulatory Surgery for the years of 1996 and 2006 were analyzed. Entries indicating the performance of knee ligamentoplasty, meniscectomy, or shoulder arthroscopy were identified and included in the sample. Temporal changes in a number of variables associated with orthopedic ambulatory surgery were assessed, including (1) the number of procedures being performed, (2) patient and health care system-related demographics, and (3) anesthesia-related variables. Results: Nationwide, the total number of ligamentoplasties, meniscectomies, and shoulder arthroscopies increased from 1996 to 2006 by 66% (n = 258, 932 to n = 428, 712), 51% (n = 456, 698 to n = 690, 164), and 349% (n = 93, 105 to n = 418, 188), respectively ( P < 0.0001). Between 1996 and 2006, the use of peripheral nerve blocks increased from 0.6% to 9.8% for meniscectomies ( P < 0.0001), from 1.5% to 13.7% for ligamentoplasties ( P < 0.0001), and from 11.5% to 23.9% for shoulder arthroscopies ( P < 0.0001), respectively. Neuraxial anesthesia utilization fell from 11.8% to 6.3% for meniscectomies ( P < 0.0001) and 13.6% to 7.3% for ligamentoplasties ( P < 0.0001) from 1996 to 2006, respectively. Conclusions: Substantial increases in the number of ambulatory knee and shoulder procedures occurred over time, relating to increased demand for anesthesia providers in this field. Trends toward increased use of peripheral nerve blocks may have to be considered by educators when preparing residents for practice.